Africanos escravizados na Ribeira do Itapecuru: produção de um material didático acerca da presença dos escravizados africanos na Vila de Cachias das Aldeias Altas (1754-1830) - Souza , Thalita Costa (2022)
The objective of this work is to emphasize the presence of enslaved Africans in the region of Caxias, Maranhão, which was constituted through the agricultural economy, in the period that extends from the 18th century to the first quarter of the 19th century. We seek, through this research, to point out about the characteristics, historical processes and plots that place Caxias das Aldeias Altas as a place of importance for the captaincy/province of Maranhão in the colonial period/early years of the Empire, as well as to highlight it as a black locality in the middle of Maranhão hinterland. To do so, we explored the numbers of enslaved Africans distributed in Ribeira do Itapecuru, especially in the region of Caxias, analyzing their characteristics and particularities, so that we could develop an educational product with the purpose of dialoguing in basic education about the presence of enslaved Africans in Caxias – MA. The research was developed through the cataloging and analysis of documents available in the Archive of the Court of Justice of Maranhão, the collection of Caxias and São Luís, and testimonies of quilombolas residing in the vicinity of Caxias. The construction of this product aims to perceive the presence of enslaved Africans in the region of Caxias - MA